Flp1 may function in the resolution of recombinant DNA intermediates - Phung , Thi Thu Huong; Tran , Hong Diem; Nguyen , Luong Hieu Hoa; Vo , Thanh Sang; Le , Van Minh; Nguyen , Hoang Dung (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Mus81 is a structure-selective endonuclease which constitutes an alternative pathway in parallel with the helicase-topoisomerase Sgs1-Top3-Rmi1 complex to resolve a number of DNA intermediates during DNA replication, repair, and homologous recombination. Previously, it was shown that the N-terminal region of Mus81 was required for its in vivo function in a redundant manner with Sgs1; sgs1Δmus81Δ100N cells are sensitive to DNA damaging agents. In this study, a single-copy suppressor screening to seek for a factor(s) that could rescue the drug sensitivity of sgs1Δmus81Δ100N cells was performed and revealed that Flp1, a site-specific recombinase 1 encoded on the 2-micron plasmid was a suppressor. This result suggests a function of Flp1 in coordination with Mus81 and Sgs1 to resolve the recombinant DNA intermediates.